(untitled) (Dhaka University Journal of Biological Sciences, 2014)
The propagation, antibacterial activity and phytochemical profiles of Litsea glutinosa have been focused. Percentage of viable seed was 70 by tetrazoliumchloride staining technique, while germination rates were 75, 70, 55 and 20% in clay loam soil, clay loam: compost, compost and sand, respectively. Propagation of basal cutting in clay loam soil under the sun was faster than the apical stem cuttings. Both the ethanolic and water soluble extracts of the leaves and bark showed against Escherichia coli, Enterobacter intermedium, Salmonella sp., Staphylococcus aureus and Staphylococcus epidermis. Phytochemical profiling of the bark of L. glutinosa showed the presence of a number of secondary metabolites including steroids and terpenoids. The isolated compounds from ethanolic bark extract (T?1 and T?3) were identified as stigmasterol and ??sitosterol, respectively by comparing the 1H?NMR data of the isolated compounds with that of the published data. DOI: http://dx.doi.org/10.3329/dujbs.v23i2.20096 Dhaka Univ. J. Biol. Sci. 23(2): 165-171, 2014